VIABILITY AND SEEDBORNE FUNGI ASSOCIATED WITH MUSTARD SEED (Brassica nigra) IN SOUTH-EASTERN, NIGERIA - B.A. Yekini; A. O. Egbontan; O.D. Alade; J.U. Nwawuisi (The Bioscientist, 2022)
Assessment of viability and seedborne fungi associated with mustard seed sold within south-eastern, agro-ecological zone of Nigeria was conducted at Plant Pathology Laboratory, Federal College of Agriculture, Ishiagu, Ebonyi State, Nigeria. Twenty mustard seed genotypes collected from south-eastern agro-ecological zone were arranged in a Completely Randomised Design (CRD) and replicated three times using moist filter paper and Potato Dextrose Agar (PDA) to determine the viability level and seedborne fungi. Data collected were subjected to analysis of variance and the means were separated using Tukey at P<0.05. The results revealed that Alternariaspecies, Fusariumoxysporum, Aspergillus niger, Aspergillus flavus, Penicilliumspecies, and Rhizopusstoloniferwere recovered from mustard seeds. Fusariumoxysporumwas prevalent among the six fungus organisms. YKM21-GA1/EN (81.67%) had the highest germination percentage, followed by YKM21-NPO/AN (80.00%), while YKM21-IS/IM (0.00%) had the least. The results of the vigour index showed that KM21-HG2/EN (231.90%) had the highest vigour index, followed by KM21-OH/AB (184.477%), while YKM21-IS/IM (0.00) had the least. The study concluded that internal seed-borne fungal organisms as per the effect of fungal isolation need to be addressed earlier before storing the seeds.This could be accomplished by treating the seeds with the appropriate fungicide, depending on the pathogen responsible for disease infection.